Spatiotemporal pattern of ENSO-induced modulation on landscape fires over Pacific Rim from 2001 to 2020 - Fang-Zhou Li; Ning-Ran Li; Martin J. Wooster; Wen-Shi Lin; Tao Xue; Tong Zhu (Advances in Climate Change Research)
While El Niño-Southern Oscillation (ENSO) modulates landscape fire activities across the Pacific Rim, the detailed patterns and mode-specific variations of these effects remain poorly understood. This study aims to address that gap by systematically assessing the spatiotemporal variations in burned areas from 2001 to 2020 during different modes of ENSO, namely, Eastern Pacific (EP) El Niño, EP La Niña, Central Pacific (CP) El Niño and CP La Niña. We evaluate the modulation patterns using classical correlation and cross-spectrum analyses, focusing on five hotspot regions: Temperate North America (TENA), Southern Hemisphere South America (SHSA), Northern Hemisphere South America (NHSA), Equatorial Asia (EQAS) and Australia and New Zealand (AUST). El Niño and La Niña exhibit asymmetrical opposite effects on burned areas, as expected. The findings reveal spatial non-uniformity in the impact of ENSO on landscape fires, with La Niña enhancing burned areas in TENA and SHSA, whereas El Niño predominantly affects AUST, EQAS and NHSA. CP and EP ENSO events differ in intensity and their large-scale circulation patterns. These differences cause notable variations in the regional burned area. Water vapour redistribution emerges as the key driver. The study emphasises the heterogeneity in ENSO modes in regulating landscape fires, providing insights for future landscape fire risk assessment and prevention efforts under climate change.